2008
DOI: 10.2215/cjn.02570607
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Protein-Bound Solutes Indican and P-Cresol Sulfate by Peritoneal Dialysis

Abstract: Background and objectives: Protein-bound solutes are poorly cleared by peritoneal dialysis. We examined the hypothesis that plasma concentrations of bound solutes would therefore rise as residual renal function is lost.Design, setting, participants, & measurements: Clearances of urea indican and p-cresol sulfate were measured in peritoneal dialysis patients with and without residual function.Results: In patients with residual function, protein binding restricted the peritoneal indican and p-cresol sulfate clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 20 publications
5
85
2
Order By: Relevance
“…dietary, differences explained the observations. The contribution of peritoneal clearance to the total removal of protein-bound solutes such as indoxyl sulfate was rather limited, confirming earlier data (13,21), which point out that the removal of protein-bound , and renal (panel C) mass removal with APD (automated peritoneal dialysis) versus CAPD (continuous ambulatory peritoneal dialysis) for urea (0.1g/week), creatinine (CREA) (cg/week), UA (uric acid) (cg/week), P (phosphorus) (cg/week), β 2 M (beta-2-microlglobulin) (mg/week), HA (hippuric acid) (cg/week), IS (indoxyl sulfate) (mg/ week), IAA (indole acetic acid) (0.1 mg/week), PCS (p-cresyl sulfate) (mg/week), free HA (cg/week), free IS (mg/week), free IAA (0.1mg/week), free PCS (mg/week), and TP (total protein) (0.1g/week). We observed better phosphate removal during CAPD as compared to higher volume APD, mainly because of improved renal clearance, confirming other literature data (20,22).…”
Section: Discussionsupporting
confidence: 89%
“…dietary, differences explained the observations. The contribution of peritoneal clearance to the total removal of protein-bound solutes such as indoxyl sulfate was rather limited, confirming earlier data (13,21), which point out that the removal of protein-bound , and renal (panel C) mass removal with APD (automated peritoneal dialysis) versus CAPD (continuous ambulatory peritoneal dialysis) for urea (0.1g/week), creatinine (CREA) (cg/week), UA (uric acid) (cg/week), P (phosphorus) (cg/week), β 2 M (beta-2-microlglobulin) (mg/week), HA (hippuric acid) (cg/week), IS (indoxyl sulfate) (mg/ week), IAA (indole acetic acid) (0.1 mg/week), PCS (p-cresyl sulfate) (mg/week), free HA (cg/week), free IS (mg/week), free IAA (0.1mg/week), free PCS (mg/week), and TP (total protein) (0.1g/week). We observed better phosphate removal during CAPD as compared to higher volume APD, mainly because of improved renal clearance, confirming other literature data (20,22).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, aside from renal solute clearance, RKF has been known to be valuable in volume control, middle molecule clearance, and nutritional aspects (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the basis of these findings, preservation of adequate RKF has emerged as a pivotal strategy in the treatment of patients on dialysis, because loss of RKF cannot be superseded by increasing dialysis dose.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RKF increases renal salt and water excretion, mitigating the adverse effect of chronic volume overload (13,14). Greater clearance of middle molecule, including b 2 -microglobulin (B2M), and protein-bound uremic toxins, including p-cresol sulfate and indoxyl sulfate (15)(16)(17)(18)(19), better phosphate control (20,21), nutritional benefit (22,23), and better anemia control (10,21) are also thought to be closely associated with beneficial effect of RKF.…”
Section: Introductionmentioning
confidence: 99%
“…Renal clearance might contribute up to 80% of total clearance of PCS in PD patients (6). Surprisingly, in a recent cross-sectional study involving 34 PD patients, Pham et al (7) reported that serum concentrations of PCS were similar in anuric and non-anuric patients and that serum concentrations of IndS were modestly increased in anuric patients only. The authors raised the hypothesis that lower PCS and IndS generation rates were obscuring the consequences of decreased renal clearance.…”
mentioning
confidence: 97%